Ruderal vegetation of Ukraine: state of research, problems and prospects (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The present paper focuses on analyzing the urgency of the research of ruderal vegetation in Ukraine. Aspects of the relevance of ruderal vegetation’s research are discussed. The main objective of this paper is to the review and analysis of the current state of investigations of ruderal vegetation in Ukraine. It is estimated and defined the further researches. The main stages and concepts (floral, phytocoenotic, restructuring) are carried out. It is shown that ruderal vegetation is investigated in Ukraine fragmentarity. It is identified the urgent concepts of investigation: continued geobotanical researches in the region to accumulate, comparison and synthesis of data and the development of theoretical issues of syntaxonomy, synphytoindication, ordination of ruderal vegetation and geobotanical zoning. Special attention is given to the optimization of industrial landscapes in particular in Kriviy Rih. It is stated that phytoremediation measures for affected as a result of industrial development lands should be directed to the creation of zonal type cenoses. Analysis of history of ruderal vegetation’s researches in Ukraine points to the complexity and ambiguity of the problems associated with its study and, at the same time – the urgent need to solve it.
Keywords: ruderal vegetation, history of investigations, Ukraine.